Simulasi Perancangan Solar Tracker Pada Pembangkit Listrik Wind-Solar - Dani Suryana Setiyawan; Djuniadi Djuniadi; Esa Apriaskar (PTE FTK UIN Ar-Raniry, 2021)
The research was conducted to explain how to design a simulation of Solar tracker on Wind-Solar hybrid technology. The simulation were carried out with proteus software simulation. Solar tracker has four LDR sensors and an Arduino Uno Microcontroller which assist the Solar tracker to estimating position of the sun to use a servo motor for solar cell movement. For the result, When the upper light intensity (LDR 1 and LDR 2) is greater than the bottom (LDR 3 and LDR 4), solar cell will move upwards, and vice versa. When the light intensity of the left (LDR 1 and LDR 3) is greater than the right (LDR 2 and LDR 4), solar cell will move to the left, and vice versa. From the research, it could concluded that Solar Tracker can be applied to Wind-Solar technology solar cells